Implications of music in modern medicine - Rajendran, Tara (Research and Humanities in Medical Education, 2021)
Though rarely a stand-alone treatment, music’s ability as an adjunct to standard treatment in increasing the quality of life has been acknowledged for decades. At first glance, the role of music in medicine may seem amorphous; however, with advancements in science, our understanding of the physiology and neurochemistry of music in relation to the human brain has expanded. Listening to and playing music involves an intriguing combination of virtually every human cognitive function. Music’s inherent ability to evoke emotions is the rationale behind music-induced goose-bumps and ‘chills of euphoria’. The psycho-neuro-endocrinology of music is a fascinating and growing field of research. In the last decade, there has been burgeoning clinical evidence on the measurable effects of music therapy over a broad spectrum of medical specialties including neurology, cardiology, psychiatry, and palliative oncology. Perhaps it is time for physicians to consider an evidence-based musical intervention as routine adjunctive therapy.